2007
DOI: 10.1007/s00595-007-3534-4
|View full text |Cite
|
Sign up to set email alerts
|

Signet-Ring Cell Carcinoma of the Ampulla of Vater: Report of a Case

Abstract: Signet-ring cell carcinoma (SRCC) of the ampulla of Vater is uncommon, and only 13 cases have been previously described. We herein report a rare case of a 43-year-old woman with SRCC in the ampulla of Vater. Although this histologic type of cancer generally predicts a poor prognosis elsewhere in the gastrointestinal tract, the present patient has survived with no evidence of recurrence for 7.5 years. The patient was hospitalized for pruritus and jaundice. She underwent a pancreaticoduodenectomy with an extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 15 publications
(17 reference statements)
0
20
1
8
Order By: Relevance
“…In case of recurrence, survival appears to be limited to median time of 12 months [4,18,19]. Our case, 35th in number, adds to the very limited number of case reports of the ampullary signet ring cells carcinomas.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…In case of recurrence, survival appears to be limited to median time of 12 months [4,18,19]. Our case, 35th in number, adds to the very limited number of case reports of the ampullary signet ring cells carcinomas.…”
Section: Discussioncontrasting
confidence: 39%
“…Overall survival among all reported patients with pure signet ring carcinoma was 24.9 months (range 6-132 months). About 30 % of reported cases had no signs of recurrence when followed up at 1 year [4]. Pattern of recurrence appears to be variable, with distant metastasis scarcely reported in the literature as a first presentation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Less than 15 cases have been described in the literature. Akatsu [4] has summarized the previous 14 cases (eight men and six women) and concluded that the median age at diagnosis was 57 years (range, 32-83 years), approximately 15 years older than SRCC of the stomach, but similar to the median age for SRCC of the large bowel. Our case was a 38-year-old woman.…”
Section: Discussionmentioning
confidence: 95%
“…However, it is unclear whether the prognosis of a patient with SRCC is worse than that of patients with ordinary carcinoma occurring in the ampulla of Vater, because of the small number of cases so far reported. A patient has been reported to survive for 7.5 years after radical resection, and the author has suggested that long-term survival is possible in ampullary SRCC without nodal involvement [4] . A 58-year-old patient lived for 134 mo after resection and had no evidence of recurrence [7] .…”
Section: Discussionmentioning
confidence: 99%